Uma proposta pedagógica utilizando sala de aula invertida no ensino da óptica geométrica: a questão da emoção em sala de aula - Rosseto, Fernando [UNESP] (2020)
The undeniable changes in the profile of students in recent decades are provided mainly by the intense action of the media and new technologies in their daily lives. The early and inordinate contact with this vast amount of information is resulting in restless, anxious young people unable to cope with both emotions and decision-making, facts that instantly reflect on the school environment, the relationships among teachers, students and program content as well as the cognitive development of children and adolescents. In particular, physics presents itself as unattainable and incomprehensible knowledge for most of these twenty-first-century students, who often complete the high school cycle without even abstracting elementary concepts of the subject and with an incalculable stressful burden. Thus, using the elaboration and application of a didactic sequence that contemplates the management of emotions and active methodologies, specifically the inverted classroom, it was intended through this work, to correlate the development of emotional intelligence of students and teachers during the physics classes. The results obtained were satisfactory, since they allowed concluding that the development of emotional intelligence is fully possible to be combined with the study of physics, motivating and instigating students to scientific knowledge. The dissertation product is presented as the didactic sequence containing all the activities developed and the results obtained in classes on the content "Introduction to Geometric Optics".